Menuju Integrasi Ekonomi ASEAN: Implementasi Local Currency Settlement antara Indonesia, Malaysia, dan Thailand - Syifa, Safina Rahma (Jurnal Ilmiah Wahana Pendidikan, 2024)
The cooperation between Indonesia, Malaysia and Thailand has been exists for a long time since the beginning of the formation of ASEAN. Local currency settlement framework agreement between the three countries exists to help increasing the use of local currency (Indonesia Rupiah, Malaysia Ringgit, and Thailand Baht) in trade transactions between themselves. The three countries are used to conducting international trade transactions using foreign currencies instead of local currencies, especially US Dollar. Therefore, the Local Currency Settlement (LCS) framework was made to reduce dependence on US Dollar. The LCS framework then also helps in increasing sub-regional trade between Indonesia, Malaysia, and Thailand, and also encourage investment between the countries.